Modernizing the North Korean System - Wolf, Charles Jr.; Levin, Norman D. (RAND Corporation, 2023)
Six institutions in five countries that have key interests in North Korea's future undertook a collaborative effort to determine ways in which the North Korean system could move toward modernization. The effort produced illustrative plans, a consensus plan, and a tool kit for constructing alternative plans for stimulating the modernization of the North Korean system.